INNOVATIVE METHODS OF TEACHING ESP LEARNERS (Multidisciplinary Journal of Science and Technology, 2024)
English for Specific Purposes (ESP) has changed dramatically in the last few years, and creative teaching strategies are now essential to raising student engagement and improving results. This article examines a number of cutting-edge techniques used in ESP training, with a focus on the use of technology, learner-centered strategies, and real materials. We demonstrate the efficacy of these approaches in addressing the unique requirements of ESP learners with an extensive analysis of recent research and real-world experiences. The essay ends with suggestions for teachers who want to use these tactics in their classrooms.